MMrgprA3/mMrgprC11/hMrgprX1: Potential therapeutic targets for allergic contact dermatitis–induced pruritus in mice and humans. (8th February 2022) - Li, Fengxian; Wang, Changming; Hu, Danyou; Zhang, Xinyu; Shen, Ran; Zhou, Yuan; Yang, Yan; Zhu, Chan; Tang, Zongxiang; Yu, Guang
Abstract: Background: Although the Mas‐related G‐protein–coupled receptors (Mrgprs) play essential roles in itch detection, their contribution to allergic contact dermatitis (ACD)–associated itch remains unclear. Objectives: To investigate whether Mrgprs are involved in ACD and whether Mrgprs can be identified as potential therapeutic targets. Methods: Mrgpr‐clusterΔ –/– mice and human MrgprX1 ( hMrgprX1 ) transgenic mice were used to evaluate the function of Mrgprs in oxazolone‐induced ACD. Results: Utilizing an ACD model, we found that Mrgpr‐clusterΔ –/– mice display significantly reduced pruritus. Among 12 Mrgprs deleted in Mrgpr‐clusterΔ –/– mice, the expression of MrgprC11 and MrgprA3 was significantly increased in the ACD model, which also innervated the skin and spinal cord at higher‐than‐normal densities. The proportions of dorsal root ganglia neurons responding to bovine adrenal medulla peptide 8‐22 and chloroquine were also remarkably increased in the ACD model, resulting in enhanced itch behaviour. To study the function of human Mrgprs in ACD‐induced itch, we used hMrgprX1 transgenic mice, which rescued the severe itch defect of Mrgpr‐clusterΔ –/– mice in the ACD model. Remarkably, pharmacological blockade of hMrgprX1 significantly attenuates ACD itch in hMrgprX1 transgenic mouse. Conclusions: Our study provides the first evidence that Mrgprs are involved in ACD‐induced chronic itch, which provides new avenues for itch management in ACD. Abstract : Oxazolone‐induced allergic contact dermatitis (ACD) pruritus partly depends on the expression of Mrgprs. ACD induces chronic itch and hyperkinesis through enhancing the expression and the activity of MrgprC11 and MrgprA3 in dorsal root ganglion neurons. hMrgprX1 rescues diminished scratching behaviour of Mrgpr‐clusterΔ –/– mice in ACD, and JHU739, the antagonist of hMrgprX1, significantly attenuates ACD‐associated itch in hMrgprX1 transgenic mice.